Impact of Treatment Modalities upon Survival Outcomes in Skull Base and Clival Chordoma: An NCDB Analysis - Muhonen, Ethan G.; Yasaka, Tyler M.; Lehrich, Brandon M.; Goshtasbi, Khodayar; Papagiannopoulos, Peter; Tajudeen, Bobby A.; St John, Maie A.; Harris, Jeremy P.; Hsu, Frank P.K.; Kuan, Edward C. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Objectives Skull base chordomas are locally aggressive malignant tumors derived from the notochord remnant. There are limited large-scale studies examining the role and extent of surgery and radiation therapy.Design Analysis of the National Cancer Database (NCDB) was performed to evaluate the survival outcomes of various treatments, and to assess for predictors of overall survival (OS).Participants This is a retrospective, population-based cohort study of patients diagnosed with a clival/skull base chordoma between 2004 and 2015 in the NCDB.Main Outcome Measures The primary outcome was overall survival (OS).Results In all, 468 cases were identified. Forty-nine percent of patients received surgery and 20.7% had positive margins. Mean age at diagnosis was 48.4 years in the surgical cohort, and 55% were males. Of the surgical cohort, 33.8% had negative margins, 20.7% had positive margins, and 45.5% had unknown margin status. Age ≥ 65 (hazard ratio [HR]: 3.07; 95% confidence interval [CI]: 1.63–5.76; p < 0.001), diagnosis between 2010 and 2015 (HR: 0.49; 95% CI: 0.26–0.90; p = 0.022), tumor size >5 cm (HR: 2.29; 95% CI: 1.26–4.15; p = 0.007), and government insurance (HR: 2.28; 95% CI: 1.24–4.2; p = 0.008) were independent predictors of OS. When comparing surgery with or without adjuvant radiation, no survival differences were found, regardless of margin status (p = 0.66).Conclusion Surgery remains the mainstay of therapy. Advanced age (>65 years), large tumor size, and government insurance were predictors of worse OS. Whereas negative margins and the use of adjuvant radiation did not appear to impact OS, these may very well reduce local recurrences. A multidisciplinary approach is critical in achieving optimal outcomes in this challenging disease.
Keywords: clival chordoma; skull base chordoma; notochord tumors; radiation; margins; skull base surgery; surgical outcomes; insurance status; national cancer database